Delayed chest wall abscess after blunt trauma chest leading to multi-organ failure: A case report - Binayak Deb; V.M. Balasubramani; Ram Varaham; Ramesh Vaidyanathan (Trauma Case Reports)
Blunt Trauma Chest (BTC) is a common cause of morbidity and mortality in trauma patients. Although rib fractures, haemothorax, pneumothorax and lung contusions are often found in tandem in BTC, delayed necrotising soft tissue infection (NSTI) without any penetrating injuries or overt puncture wounds have rarely been reported. We report a 61-year-old patient with uncontrolled diabetes, admitted after a motor vehicle collision with head, chest and lower limb injuries and discharged after 9 days of stay in the hospital. He returned with NSTI of the chest wall around a week later with a fulminant clinical course ultimately leading to septic shock, multi-organ dysfunction and demise of the patient.